Drinking and mortality: long‐term follow‐up of drinking‐discordant twin pairs. (13th November 2015) - Sipilä, Pyry; Rose, Richard J.; Kaprio, Jaakko
Abstract: Aims: To determine if associations of alcohol consumption with all‐cause mortality replicate in discordant monozygotic twin comparisons that control for familial and genetic confounds. Design: A 30‐year prospective follow‐up. Setting: Population‐based older Finnish twin cohort. Participants: Same‐sex twins, aged 24–60 years at the end of 1981, without overt comorbidities, completed questionnaires in 1975 and 1981 with response rates of 89 and 84%. A total of 15 607 twins were available for mortality follow‐up from the date of returned 1981 questionnaires to 31 December 2011; 14 787 twins with complete information were analysed. Measurements: Self‐reported monthly alcohol consumption, heavy drinking occasions (HDO) and alcohol‐induced blackouts. Adjustments for age, gender, marital and smoking status, physical activity, obesity, education and social class. Findings: Among twins as individuals, high levels of monthly alcohol consumption (≥ 259 g/month) associated with earlier mortality [hazard ratio (HR) = 1.63, 95% confidence interval (CI) = 1.47–1.81]. That association was replicated in comparisons of all informatively drinking‐discordant twin pairs (HR = 1.91, 95% CI = 1.49–2.45) and within discordant monozygotic (MZ) twin pairs (HR = 2.24, 95% CI = 1.31–3.85), with comparable effect size. Smaller samples of MZ twins discordant for HDO and blackouts limited power; a significant association with mortality was found for multiple blackouts (HR = 2.82, 95% CI = 1.30–6.08), but not for HDO. Conclusions: The associations of high levels of monthly alcohol consumption and alcohol‐induced blackouts with increased all‐cause mortality among Finnish twins cannot be explained by familial or genetic confounds; the explanation appears to be causal.